1994
DOI: 10.1073/pnas.91.3.1183
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative susceptibility of low density lipoprotein subfractions is related to their ubiquinol-10 and alpha-tocopherol content.

Abstract: The conjugated polyene fatty acid parinaric acid (PnA) undergoes a stoichiometric loss in fluorescence upon oxidation and can be used to directly monitor peroxidative stress within lipid environments. We evaluated the course of potentially atherogenic oxidative changes in low density lipoproteins (LDL) by monitoring the oxidation of PnA following its incorporation into buoyant (p = 1.026-1.032 g/ml) and dense (p = 1.040-1.054 g/ml) LDL subfractions. Copperinduced oxidation of LDL-associated PnA exhibited an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 38 publications
8
57
2
1
Order By: Relevance
“…Lipid peroxidation in beef heart mitochondrial membranes was measured as the loss of fluorescence of cPA, a polyunsaturated fatty acid that partitions into phospholipid bilayers and loses its fluorophore on oxidation, so it can be used as a convenient marker of phospholipid peroxidation in membranes (33). AAPH led to a loss of cPA fluorescence that was prevented by MitoPBN (Fig.…”
Section: Fig 5 Prevention Of Initiation Of Lipid Peroxidation By MImentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation in beef heart mitochondrial membranes was measured as the loss of fluorescence of cPA, a polyunsaturated fatty acid that partitions into phospholipid bilayers and loses its fluorophore on oxidation, so it can be used as a convenient marker of phospholipid peroxidation in membranes (33). AAPH led to a loss of cPA fluorescence that was prevented by MitoPBN (Fig.…”
Section: Fig 5 Prevention Of Initiation Of Lipid Peroxidation By MImentioning
confidence: 99%
“…PBS, phosphatebuffered saline. 37°C with constant stirring (33). Beef heart mitochondrial membranes, prepared as described (34), were incubated in 50 mM KP i buffer, pH 8.0, and after 40 s, cis-parinaric acid (0.5 M) was added, and its oxidation was monitored.…”
Section: Table Imentioning
confidence: 99%
“…Finally, their uptake into macrophages to create form cells, and initiate atherogenesis, is facilitated [84]. This may explain their identification as an independent risk factor for coronary heart disease [82][83][84].…”
Section: Is Normal Pregnancy Atherogenic?[80]mentioning
confidence: 99%
“…These lipoproteins contain subfractions of various sizes, densities and compositions, which differ in their ability to initiate atherogenesis [81]. One of the subfractions of LDL (LDL-3) is small, dense LDL particles which do not bind readily to the LDL receptors and therefore remain in the circulation for longer time, penetrate the arterial intima better than do larger ones [82] and are more readily oxidized, probably because they contain less vitamin E and other antioxidants [83]. Finally, their uptake into macrophages to create form cells, and initiate atherogenesis, is facilitated [84].…”
Section: Is Normal Pregnancy Atherogenic?[80]mentioning
confidence: 99%
“…Recently, in subjects with FCH, total LDL was found to be more prone to in vitro oxidation owing to the predominance of dense LDL particles. In addition, it was suggested that the decreased redox status of coenzyme Q10 in LDL from subjects with a dense LDL subfraction profile reflected the presence of already in vivo modified LDL owing to lipid peroxidation in the circulation [125,126].…”
Section: Fch and Premature Atherogenesismentioning
confidence: 99%